Influence of high-bromine poultry products on clinical-biochemical blood parameters of white rats - Koreneva, Y. M.; Orobchenko, O. L.; Romanko, M. Y.; Malova, N. G.; Sachuk, R. M.; Gutyj, B. V.; Radzykhovskyi, M. L. (Regulatory Mechanisms in Biosystems, 2023)
Bromine content in fodder and water for laying chickens in Ukraine gradually increasing, thereby accumulating in the poultry production (eggs and meat): according to the data, intake of bromine with chicken eggs in 2020 has almost doubled, compared with 2016. Taking into account the ability of bromine to accumulate and the scales of consumption of poultry products, it is relevant to study the effects of high bromine concentration on the level of thyroid hormones and clinical-biochemical parameters of blood of white rats. At the laboratory of Toxicological Monitoring of the National Scientific Center the Institute of Experimental and Clinical Veterinary Medicine and the Department of Experimental Pharmacology and Toxicology of the State Institution V.Y. Danylevskyi Institute of Problems of Endocrine Pathology of the National Academy of Medical Sciences of Ukraine, we carried out studies on white outbred male rats (n = 144). The diet of experimental groups was supplemented with eggs and meat containing high bromine concentration. We determined increase in the coefficients of liver weight and decrease in the coefficients of lung weight in the experimental rats. Moreover, we determined changes in the biochemical blood profile, in particular: after egg consumption, there occurred 20.0–22.0% decrease in the enzymatic activity of alanine aminotransferase, 23.0–48.4% in the activity of aspartate aminotransferase, and on average 21.3% decrease in alkaline phosphatase, compared with the control; after meat consumption, the level of total proteins decreased by 8.6%, glucose by 12.2–14.5%, also there were 13.8–18.5% decrease in the activity of alanine aminotransferase and 12.1–83.0% increase in the activity of aspartate aminotransferase on the 28th day, and 23.2–35.3% decrease in the activity of alkaline phosphatase. After the intake of both poultry products, the blood serum of animals was observed to have decrease in the level of overall thyroxine and overall triiodothyronine (1.3 times on average, depending on the period of study). The results of the studies can help in prediction and timely alleviation of the negative impact of poultry products with high bromine content on the human organism.